PITX2‐dependent gene regulation in atrial fibrillation and rhythm control. (25th April 2017) - Syeda, Fahima; Kirchhof, Paulus; Fabritz, Larissa
Abstract : Reduced Pitx2 expression leads to proarrhythmic cardiac electrical atrial remodelling. Several different murine models of Pitx2 downregulation have shown atrial action potential shortening and a depolarised atrial resting membrane, two established causes of arrhythmia. Alterations in calcium and potassium handling genes and TASK‐like background currents have been postulated to contribute in different models. The type of electrical remodelling may be a predictor of the anti‐arrhythmic effectiveness of rhythm control therapy. Sodium currents may also contribute. IRK, Inwardly rectifying potassium channels; K2P, Two‐pore domain potassium channels; TASK, TWIK‐related acid‐sensitive K + channel. Abstract: Atrial fibrillation (AF) is a common arrhythmia. Better prevention and treatment of AF are needed to reduce AF‐associated morbidity and mortality. There are several major mechanisms that cause AF in patients, including a genetic predisposition to develop AF. Genome‐wide association studies have identified genetic variants associated with AF populations, with the strongest hits clustering on chromosome 4q25, close to the gene for the homeobox transcription factor PITX2. The effect of these common gene variants on cardiac PITX2 mRNA is currently under study. PITX2 protein regulates right–left differentiation of the embryonic heart, thorax and aorta. PITX2 is expressed in the adult left atrium, but much less so in other heart chambers. Pitx2 deficiency results in electrical and structural remodelling, and impaired repair of the heart in murine models, all of which may influence AF through divergent mechanisms. PITX2 levels and single nucleotide polymorphisms on chromosome 4q25 may also be a predictor of the effectiveness of anti‐arrhythmic drug therapy.